Biochemical characterization of an alcohol dehydrogenase from Ralstonia sp. Issue 7 (22nd February 2013) - Kulig, Justyna; Frese, Amina; Kroutil, Wolfgang; Pohl, Martina; Rother, Dörte
Abstract Stereoselective reduction towards pharmaceutically potent products with multi‐chiral centers is an ongoing hot topic, but up to now catalysts for reductions of bulky aromatic substrates are rare. The NADPH‐dependent alcohol dehydrogenase from Ralstonia sp. (RADH) is an exception as it prefers sterically demanding substrates. Recent studies with this enzyme indicated outstanding potential for the reduction of various alpha‐hydroxy ketones, but were performed with crude cell extract, which hampered its detailed characterization. We have established a procedure for the purification and storage of RADH and found a significantly stabilizing effect by addition of CaCl2. Detailed analysis of the pH‐dependent activity and stability yielded a broad pH‐optimum (pH 6–9.5) for the reduction reaction and a sharp optimum of pH 10–11.5 for the oxidation reaction. The enzyme exhibits highest stability at pH 5.5–8 and 8–15°C; nevertheless, biotransformations can also be carried out at 25°C (half‐life 80 h). Under optimized reaction parameters a thorough study of the substrate range of RADH including the reduction of different aldehydes and ketones and the oxidation of a broad range of alcohols was conducted. In contrast to most other known alcohol dehydrogenases, RADH clearly prefers aromatic and cyclic aliphatic compounds, which makes this enzyme unique for conversion of space demanding substrates. Further, reductions are catalyzed with extremely high stereoselectivity (>99% enantio‐ and diastereomeric excess). In order to identify appropriate substrate and cofactor concentrations for biotransformations, kinetic parameters were determined for NADP(H) and selected substrates. Among these, we studied the reduction of both enantiomers of 2‐hydroxypropiophenone in more detail. Biotechnol. Bioeng. 2013; 110: 1838–1848. © 2013 Wiley Periodicals, Inc.